Assessment of early maturity based on per cent reduction in yield by advancing date of harvest in groundnut (Arachis hypogaea L.): EARLY MATURITY IN GROUNDNUT - CHUNI LAL; K HARIPRASANNA (Journal of Oilseeds Research, 2013)
Breeding of short duration groundnut (Arachis hypogaea L.) varieties with enhanced productivity is a priority area in the semi-arid tropical regions to evade the end-season moisture deficit stress and for summer cultivation where the harvesting of groundnut coincides with the on-set of monsoon. Eighteen advanced breeding lines were evaluated during rainy and summer seasons for productive capacity and earliness in maturity by estimating the relative reduction in yield and associated traits due to advanced harvesting by 10 or 20 days over normal harvest. During rainy season the test genotypes were also compared with two popular varietiesJL 24 and HNG 10 as checks. Harvesting the genotypes 20 days ahead of normal harvest lead to considerable loss in pod and kernel yield, the reduction being larger in summer. When harvesting was advanced by 10 days the relative yield reduction was considerably lower in some of the genotypes (1-4% pod and 3-4% kernel yield reduction during rainy season), and six genotypes recorded superior yield coupled with earliness in comparison to the best check. The genotypes PBS 11029, PBS 21031, PBS 30076, PBS 11066, PBS 15004 and PBS 28008 were found early in maturity during rainy season and PBS 21031 during summer asthey registered negligible lossin yield when harvesting was advanced. The proposed concept of least reduction in yield and its component traits when harvested early coupled with high productivity may be used as a field technique forscreening large number of advanced breeding linesto identify early and high productive genotypes.